Eligibility for marine omega-3 fatty acid supplementation after acute coronary syndromes - Follonier, Cédric; Rabassa, Gabriel; Branca, Mattia; Carballo, David; Koskinas, Konstantinos; Heg, Dik; Nanchen, David; Räber, Lorenz; Klingenberg, Roland; Haller, Moa Lina; Carballo, Sebastian; Windecker, Stephan; et al. (Atherosclerosis plus, 2024)
The 2019 European Society of Cardiology guidelines for the management of dyslipidemia consider the use of high-dose marine omega-3 fatty acid (FA) eicosapentaenoic acid (EPA) supplementation (icosapent ethyl 2 × 2g/day) to lower residual cardiovascular risk in high-risk patients with hypertriglyceridemia. This study aimed to assess the eligibility for omega-3 FA-EPA supplementation in patients with acute coronary syndromes (ACS). In a prospective Swiss cohort of patients hospitalized for ACS, eligibility for marine omega-3 FA-EPA, defined as plasma triglyceride levels ranging from 1.5 to 5.6 mmol/l, was assessed at baseline and one-year follow-up and compared across subgroups. Lipid-lowering therapy intensification with statin and ezetimibe was modelled to simulate a hypothetical systematic treatment and its effect on omega-3 FA-EPA supplementation eligibility. Of 2643 patients, 98 % were prescribed statin therapy at discharge, including 62 % at a high-intensity regimen; 93 % maintained it after one year, including 53 % at a high-intensity regimen. The use of ezetimibe was 3 % at discharge and 7 % at one year. Eligibility was observed in 32 % (32 % men, 29 % women) one year post-ACS. After modelling systematic treatment with statins, ezetimibe, and both, eligibility decreased to 31 %, 25 % and 24 %, respectively. Eligibility was higher in individuals aged <70 (34 vs 25 %), smokers (38 vs 28 %), diabetics (46 vs 29 %), hypertensive (35 vs 29 %), and obese patients (46 vs 22 % for normal weight), all with p-values <0.001. In a contemporary Swiss cohort of patients with ACS, up to 32 % would be eligible for omega-3 FA-EPA supplementation one year after ACS, highlighting an opportunity to mitigate residual cardiovascular risk in patients with ACS and hypertriglyceridemia. •High-dose omega-3 fatty acid eicosapentaenoic acid (FA-EPA) supplementation has been shown to lower cardiovascular risk in high-risk patients with hypertriglyceridemia.•Up to 1 in 3 patients were eligible for omega-3 FA-EPA supplementation one year after acute coronary syndromes.•Eligibility for omega-3 FA-EPA is higher in those <70 years old and in smokers, diabetics, hypertensive, and obese patients.